Turkish-Russian Relations in 21st Century: Problems of Development - Ruilin Xu; S. S. Kolegov (Научный диалог)
This article provides a brief overview of the development of Russian-Turkish relations in the 21st century against the backdrop of changes in Turkey’s domestic political situation at the turn of the 20th and 21st centuries. Special attention is paid to the evolution of Turkey’s foreign policy strategy. It is noted that the Russian Federation is a particularly important partner for the Republic of Turkey. The relevance of the topic lies in the fact that currently, the relationship between the two countries continues to develop actively, despite external political challenges. At the same time, the history of Russia-Turkey contacts requires further study, as this period is not well represented in the existing literature. The novelty of this research lies in the use of new sources to study state relations. The authors of the article come to a justified conclusion that the Turkish government seeks to develop its relationship with the Russian Federation while maintaining ties with both Western and Eastern countries. This demonstrates their efforts to utilize the opportunities provided by Turkey’s geographical location, which serves as a “corridor” between various parts of Eurasia.